HUBUNGAN USIA DAN MASA KERJA DENGAN NILAI AMBANG DENGAR PEKERJA YANG TERPAPAR BISING DI PT. X SIDOARJO - Winda Wahyuni Putri; Tri Martiana (The Indonesian Journal of Occupational Safety and Health, 2016)
One factor that could result in disturbance of health in the process production is noise the following noise interferes due to the use of thr machine production. The purpose of this study was to analyze the correlation of age and working period with hearing threshold value of workers exposed to noise in the unit of production Steel Melting Shop PT. X Sidoarjo. This study used cross-sectional design. Population of the study is labor in the production of Steel Melting Shop PT. X Sidoarjo as many as 108 employees. Samplesin this study are 28 employees, taken by simple random sampling with criteria inklusi willing to be the sample of the research and not experience pain (no history of ear disease and had never experienced head trauma). Variables independent is age, and working period. Variable dependent is a hearing threshold value. Noise measurements in the unit production of Steel Melting Shop PT. X Sidoarjo show his worth beyond NAB (106 dB s/d 107 dB). Workup audiometri show 22 from 28 sample had abnormal hearing threshold value (> 25 dB). Test with correlation pearson showed relationship age and working period with hearing threshold value. Conclusion from this study is that noise in the unit production of Steel Melting Shop PT. X Sidoarjo beyond NAB and many workers had abnormal hearing threshold value as the correlation of age and working period with a worker hearing threshold value PT. X Sidoarjo. Do the rotation of workers to reduce long exposure to high risk workers exposed to noise.Keywords: age and working period, hearing threshold value, noise exposure